The role of clusters in the performance of the Mexican economy - Miriam Juarez-Torres; Jonathan Puigvert-Angulo; Francisco Zazueta-Borboa (Banco de México, 2022)
This paper follows an algorithm that considers different dimensions of linkages across service and manufacturing industries to identify a cluster configuration of the Mexican economy and analyze their role in the economic performance of regions. It identifies 24 clusters and analyzes their geographical distribution, their role in regional growth, the evolution of their employment concentration, and their spillover effects. The main findings suggest that manufacturing-oriented clusters have a strong presence in the Northern states of the country, while services-oriented clusters in the Central ones. Finally, clusters such as plastic products manufacturing; retail and eating services; food and beverage manufacturing; and, automotive show relatively high direct and indirect spillover effects on the economy.
Keywords: L60; L80; O54; 330; Clusters; Agglomeration economies; Employment concentration; Economic spillovers effects